Perencanaan Strategi Pemasaran Dalam Peluncuran Produk TEFA (Teaching Factory) di SMKN 1 Surakarta - Istyana Yulianti (Jurnal Indonesia Sosial Teknologi, 2023)
Today's increasingly fierce business competition, encourages many companies to plan innovative marketing strategies. The rapid changes in the situation that occur in the business world in this era of globalization have resulted in the level of success of a company in the past which does not guarantee its success in the future. In order to be able to compete and survive, the focus of the company's business activities and processes must remain concentrated on dynamic customer needs so that the goal of fulfilling customer needs and customer satisfaction can be fulfilled. Against this background, we as curious teachers at SMKN 1 Surakarta must take the initiative to make a breakthrough to introduce or even jump-start Tefa Saska products so that we can compete with Tefa from other schools and can even produce superior Tefa that will bring the good name of SMKN 1 Surakarta is even more famous and recognized at the National level. there are several superior TEFAs at SMKN 1 such as TUKUYA, GMV, CAFE SASKA, and STARMEDIA. The breakthroughs made include providing more innovative marketing strategies based on dynamics changes that occur in society, especially the world of education in order to win the attention of the world of education to Tefa products at SMKN 1 Surakarta. Analysis and information are limited to SMK N fi SOLORAYA. This type of research was carried out by distributing questionnaires and product sampling to 300 respondents. The results and conclusions obtained from this research include information about the behavior of consumers towards Tefa products that have been produced and have been exhibited and information about the strengths and weaknesses of Tefa products seen based on existing marketing concepts. And in the end, based on the data that has been obtained and processed, a strategic marketing plan is formulated to win market share in the community.